Moving millions : the commercial success and political controversies of Hong Kong's railways - Yeung, Rikkie (Hong Kong University Press, 2008)
This comprehensive analysis of the Hong Kong railways provides an analysis of the exceptionally profitable model followed by the MTRC and the KCRC and the social costs behind their success. The book traces the railway governance over the last thirty years as Hong Kong underwent rapid socio-economic modernisation and a unique political transition.